A discussion on provenance research with some early provenances uncovered - Voukelatos, John (KOINON: The International Journal of Classical Numismatic Studies, 2019)
Provenance research is no less important in the field of ancient numismatics than it is in art and antiquities. No doubt following on from concerns regarding looted antiquities and their repatriation by many major museums in recent years, especially in the United States of America, there has been an increased interest and awareness of provenance. Beyond these practical reasons to know of an artefacts provenance there has been a renewed interest in academia to reconstruct old antiquities collections or uncover lost provenances. Even in the area of antiquities old provenances continue to be found. For example the provenance of an important Attic red figure amphora once in the collection of Lucien Bonaparte, the Prince of Canino, Etruria and now in the Hermitage museum St Petersburg (Inv. No. GR 8056) was only discovered in 2017.